2020
DOI: 10.1080/07060661.2020.1793222
|View full text |Cite
|
Sign up to set email alerts
|

First report of Fusarium proliferatum causing crown and stem rot, and pith necrosis, in cannabis (Cannabis sativa L., marijuana) plants

Abstract: Cannabis (Cannabis sativa L., marijuana) plants grown under greenhouse or controlled environments with symptoms of leaf yellowing, leaf necrosis and defoliation were observed during 2018-2019. Additional symptoms included crown rot and internal browning or blackening of the pith tissues. Stock (mother) plants as well as plants in the vegetative and flowering stages of 15 cannabis strains (genotypes) were affected. In addition, damping-off symptoms were observed on rooted cuttings in propagation rooms. Isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Lastly, F. graminearum was recovered from bud rotinfected inflorescences from one facility sampled in September. Cannabis inflorescences previously have been reported to be infected by F. solani, F. oxysporum and F. proliferatum (Punja 2018(Punja , 2021b(Punja , 2021c, with air-or water-borne inoculum spreading from adjacent infected plants (Punja et al 2019). In the present study, the source of inoculum of F. graminearum was likely from a barley field located 150 m away from the cannabis greenhouse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, F. graminearum was recovered from bud rotinfected inflorescences from one facility sampled in September. Cannabis inflorescences previously have been reported to be infected by F. solani, F. oxysporum and F. proliferatum (Punja 2018(Punja , 2021b(Punja , 2021c, with air-or water-borne inoculum spreading from adjacent infected plants (Punja et al 2019). In the present study, the source of inoculum of F. graminearum was likely from a barley field located 150 m away from the cannabis greenhouse.…”
Section: Discussionmentioning
confidence: 99%
“…These 'bud rot' pathogens are reported to include Botrytis cinerea Pers. Fr., a widespread and destructive pathogen of cannabis and hemp (Punja et al 2019;Garfinkel 2020), as well as several species of Fusarium and Penicillium that can cause pre-and postharvest bud rots (Punja 2021a(Punja , 2021b(Punja , 2021c. Infection by Hop latent viroid can also reduce the quality of cannabis inflorescences (Bektas et al 2019;Warren et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, F. solani was recovered from six cannabis production facilities located in two provinces by sampling symptomatic stock plants, rooted cuttings, as well as plants in the vegetative stage of growth. Since the symptoms of crown discoloration, damping off, and root browning overlap with those caused by F. oxysporum and F. proliferatum reported recently (Punja 2021b(Punja , 2021c, fungal isolation and identification was conducted. Inoculation studies showed that isolates of F. solani caused root infection, damping-off and yellowing of plants.…”
Section: Discussionmentioning
confidence: 99%
“…On cannabis (Cannabis sativa L., marijuana), several species of Fusarium are reported to cause root and crown rots under greenhouse conditions. These include F. oxysporum (Punja 2021b), F. proliferatum (Punja 2021c), as well as F. solani (Punja and Rodriguez 2018). The diseases caused by the former two species have been described in detail recently, yet there are no previous studies showing the extent to which F. solani (FSSC) is present on cannabis plants and the symptoms of disease.…”
Section: Introductionmentioning
confidence: 99%
“…PCR was used to identify most of the species listed in Table S1. In addition, the elongation factor 1 (EF‐1) region was used to discriminate among Fusarium species 21,38 . For Golovinomyces causing powdery mildew and Botrytis species causing bud rot, additional molecular markers are required to differentiate between species.…”
Section: Pathogen Identificationmentioning
confidence: 99%